1986
DOI: 10.1159/000183828
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Renal Failure and Cardiovascular Autonomic Function

Abstract: Autonomic function was assessed in 67 patients with chronic renal failure using a standardized battery of five cardiovascular reflex tests. The results showed that 38 (65%) had early or definite parasympathetic abnormalities, while 14 (24%) had additional sympathetic damage. There were no significant differences between those treated conservatively (n = 19), those on continuous ambulatory peritoneal dialysis (n = 8) and those on intermittent haemodialysis (n = 40). Cardiovascular autonomic damage is widespread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 9 publications
(17 reference statements)
0
23
1
3
Order By: Relevance
“…Dys function of the parasympathetic control of the cardio vascular system appeared to be more frequent (36% inci dence) than a damage of the sympathetic control (18%). Such a degree of frequency is lower than that reported elsewhere [4,5,7], It may be explained by the selection we did excluding patients with diseases influencing the cardiovascular-reflex testing, the comparison with ageadjusted normal ranges, and by the criteria we chose to assess the presence of ANS damage.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Dys function of the parasympathetic control of the cardio vascular system appeared to be more frequent (36% inci dence) than a damage of the sympathetic control (18%). Such a degree of frequency is lower than that reported elsewhere [4,5,7], It may be explained by the selection we did excluding patients with diseases influencing the cardiovascular-reflex testing, the comparison with ageadjusted normal ranges, and by the criteria we chose to assess the presence of ANS damage.…”
Section: Discussionmentioning
confidence: 75%
“…A defective reg ulation of the heart rate, due mostly to an afferent lesion, appeared more common than damage of reflex blood pressure control in dialysis patients, and studies with adequate control subjects showed a definite parasympa thetic damage in 47-60% of patients [4][5][6][7], Pre-dialysis uraemic patients have been reported to have more exten sive disturbances of ANS than dialysis patients [8,9]. Other investigators [4] on the other hand stated that uraemic ANS dysfunction was not improved by ade quate haemodialysis, whereas successful renal transplan tation reduced the incidence of ANS derangement.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, no increase in HR was observed in renal dysfunctional dogs, in spite of the continuous reduction in MBP. It is shown that patients with renal dysfunction have autonomic dysfunction [13] and NO reduces sympathetic activity [4]. These results suggest that an excessive production of NO suppresses the sympathetic nerve activity in renal dysfunctional dogs.…”
Section: Discussionmentioning
confidence: 88%
“…A single dialysis session has no effect on autonomic function [15]. Results of the studies on the effect of chronic hemodialysis on autonomic function are contradictory, ranging from fair or excellent improvement [16, 17, 18]to indifferent change [13, 19]. However, there are few longitudinal studies on this subject.…”
Section: Discussionmentioning
confidence: 99%